A Diver-Portable Respirometry System for in-situ Short-Term Measurements of Coral Metabolic Health and Rates of Calcification - Dellisanti, Walter; Tsang, Ryan H. L.; Ang, Put; Wu, Jiajun; Wells, Mark L.; Chan, Leo L. (Frontiers in Marine Science, 2020)
Underwater visual monitoring methods are used broadly to evaluate coral reef conditions in the natural environment, but quantitative measurements of the coral holobiont has been largely restricted to photophysiological assessment of the endosymbionts. An underwater respirometer has been designed to make routine, diver-operated, non-invasive measurements at coral surfaces, but the realistic in situ accuracy and precision capabilities of this device has not been critically assessed; an essential step if these measurements are to be useful for quantifying spatial and seasonal patterns of coral metabolism. We developed specific protocols for this system to survey shallow coral colonies and detect metabolic profiles (respiration, photosynthesis, and biocalcification), diel cycles (day and night), and photosynthesis-irradiance curves. Analysis of data from in situ and laboratory-controlled conditions showed good replication among coral colonies and high precision measurements of temperature, oxygen and pH fluxes over 15-min incubation times without noticeable detrimental effects on coral health. Moreover, marked differences were observed in coral calcification rates between estuarine-influenced and coastal marine conditions, despite the absence of significant differences in visual appearance or other health indicators, revealing the system’s potential for early detection of marginally adverse conditions for coral metabolism. Its ease of operation and rapid quantification of the physiological status of the corals make this respirometer well suited for use by reef scientists, monitoring agencies, and stakeholders in biogenic reefs conservation efforts. Moreover, the high spatial and temporal resolution of these underwater respirometer data will have the potential to discriminate the effects of local stressors on coral health from those generated by broader changes associated with climate drivers.